How to Best Name a Place? Facilitation and Inhibition of Route Learning Due to Descriptive and Arbitrary Location Labels - Meilinger, Tobias; Schulte-Pelkum, Jörg; Frankenstein, Julia; Hardiess, Gregor; Laharnar, Naima; Mallot, Hanspeter A.; Bülthoff, Heinrich H. (Frontiers in Psychology, 2016)
Establishing verbal memory traces for non-verbal stimuli was reported to facilitate or inhibit memory for the non-verbal stimuli. We show that these effects are also observed in a domain not indicated before – wayfinding. Fifty-three participants followed a guided route in a virtual environment. They were asked to remember half of the intersections by relying on the visual impression only. At the other 50% of the intersections, participants additionally heard a place name, which they were asked to memorize. For testing, participants were teleported to the intersections and were asked to indicate the subsequent direction of the learned route. In Experiment 1, intersections’ names were arbitrary (i.e., not related to the visual impression). Here, participants performed more accurately at unnamed intersections. In Experiment 2, intersections’ names were descriptive and participants’ route memory was more accurate at named intersections. Results have implications for naming places in a city and for wayfinding aids.